2021
DOI: 10.1016/j.heliyon.2021.e08621
|View full text |Cite
|
Sign up to set email alerts
|

Social support and subjective well-being among postgraduate medical students: the mediating role of anxiety and the moderating role of alcohol and tobacco use

Abstract: Medical students often face pressures from various sources in the course of postgraduate studies, and these factors have a negative impact on their subjective well-being. Previous researches have revealed that social support is a vital factor influencing subjective well-being, but unfortunately the underlying mechanism for this is unclear, especially for postgraduate medical students. The current study has inspected the effects of social support on subjective well-being of postgraduate medical students, the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The results of the analysis show that religiosity, social support, and self-efficacy have a direct effect on subjective well-being. The finding concerning the influence of social support on subjective well-being aligns with Huang et al (2021), who reported a positive relationship between social support and subjective well-being. Research by Putri (2016) also showed that social support is related to subjective well-being in early adolescents.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The results of the analysis show that religiosity, social support, and self-efficacy have a direct effect on subjective well-being. The finding concerning the influence of social support on subjective well-being aligns with Huang et al (2021), who reported a positive relationship between social support and subjective well-being. Research by Putri (2016) also showed that social support is related to subjective well-being in early adolescents.…”
Section: Discussionsupporting
confidence: 79%
“…Social closeness with family and friends can increase the happiness and life satisfaction aspects of subjective well-being, while negative interactions can reduce happiness (Nguyen et al, 2016). Social support can also help to reduce anxiety in individuals when they experience problems (Huang et al, 2021) and reduce negative affect (Siedlecki et al, 2014), thus helping them to maintain their subjective well-being in difficult circumstances. Moreover, perceived social support positively influences individuals' general well-being and mental health (Cobo-Rendón et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al (2020) state that the subjective well-being can increase if social and emotional development of adolescents, including students, is strengthened by social support. Social support has also contributes students' adaptability to the conditions and problems they face and make them resilient (Bukhori et al, 2017;Huang et al, 2021;Maisyarah, 2015;Mufidah, 2017). There are three sources of social support for individuals: friends, family, and significant others (Zimet et al, 1988).…”
Section: │ 265mentioning
confidence: 99%
“…High levels of stress in undergraduate nursing students obviously lowered their overall wellness (Spurr et al, 2021). Huang et al (2021) reported that the anxiety of postgraduate medical students affected their SWB. The higher level of anxiety predicted the lower level of SWB.…”
Section: Discussionmentioning
confidence: 99%